NEEDS ANALYSIS ON THE EFFORT OF DEVELOPING STUDENTS’ CREATIVE THINKING ABILITY IN ELEMENTARY SCHOOL - pangestu, widya trio (Journal of Education Research and Evaluation, 2021)
Learning in elementary school is implemented by giving model, building willingness, as well as developing the students’ creativity in the learning process. Those are the attempts in preparing creative and competitive young generation in globalization era. In order to create educational aims in the elementary school, an innovation on learning model that can develop the students’ creative thinking aspect is required, so that it creates creativities that can be implemented in daily life in the society. Based on the observations on learning process that have been done there was no synergy yet between the aim and method as well as learning model that was used, moreover, learning process that was implemented was still teacher centered. The aims of this research are to find out: (1) The importance of creative thinking ability development, (2) students’ needs on learning resources, (3) students’ needs on alternative learning model, (4) students’ interest in learning model that develops creative thinking ability, (5) teachers’ needs on learning resources, (6) teachers’ needs on alternative learning model, (7) teachers’ interest on learning model that develops students’ creative thinking ability. Method that was used in this research is descriptive qualitative data gathering in form of questionnaires to teachers and students. The results of this research revealed that both the teachers and the students agreed on alternative learning model that is appropriate with the students’ needs to develop creative thinking. In relation to the development of elementary school creative thinking learning model can be considered as acceptable or approved.